Search 75,753 tutors
FIND TUTORS
Ask a question
0 0

needing help

Tutors, please sign in to answer this question.

2 Answers

(3x + 6) (3x - 6)
 
(x-8) (x-3)
 
I don't understand the second part of your question.

Comments

Nataliya D. was correct on the first one.  I didn't factor out the 9 first.

The correct answer was 9(x-2) (x+2).
 
9x^2-36 = (3x+6) (3x-6) = 3(x+2)(3)(x-2) = 9(x-2)(x+2)

Or the best way 9(x^2-4) = 9(x-2)(x+2). 

My apologies that in my haste I didn't COMPLETELY factor the expression.

Comment

a2 - b2 = (a - b)(a + b) 

~~~~~~~~~~     

9x2 - 36 = 9(x2 - 4) = 9(x - 2)(x + 2)